Mechanical response and parametric analysis of a deep excavation structure overlying an existing subway station: A case study of the Beijing subway station expansion - Han, Jianyong; Wang, Jun; Cheng, Cheng; Zhang, Chaozhe; Liang, Erbin; Wang, Zhikang; Song, Jae-Joon; Leem, Junsu (Frontiers in Earth Science, 2023)
The existing Beijing Pingguoyuan Subway Station was extended through the extension project. The extension excavation is located above the existing station directly. There are complex interactions between the existing structure and the retaining pile wall of the excavation. Based on this project, three-dimensional finite element models were established to investigate the mechanical characteristics of embedded and non-embedded retaining pile walls. Meanwhile, the parametric analysis were carried out for both pile walls.. The stress and deformation characteristics of the retaining pile walls and existing structure were analyzed. The results show that when the bottom of the non-embedded retaining pile walls are connected to the existing structure, the uplift of the existing structure is basically constant, but the maximum displacement of the pile is increased by about 2.7 times, and the bending moment of the pile is reduced to 57.1% of the connection condition. As the distance between the embedded retaining pile wall and the existing station increases, the uplift of the existing station increases linearly, while the part of the soil between the pile and the station shows a nonlinear increase trend. The displacement of the embedded retaining pile wall increases and the inner force decreases. When the distance is greater than 4.7m, displacement and force of the pile basically no longer change. The effect of the pile embedded depth on the force and deformation of the pile is mainly in the lower part of the pile. As the embedded depth increases, the maximum displacement decreases by about 16.9%, the maximum bending moment decreases, and the maximum negative bending moment increases.